PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PASIEN RAWAT INAP DALAM MENGGUNAKAN JASA - Hardono, Hardono Hardono (JURNAL ILMU MANAJEMEN, 2015)
Background: in Indonesia the hospital as one of the health care system in outline to provide services to mesyarakat. Many factors are considered in choosing, but one way to attract customers and win the competition is to provide quality services in accordance with customer wishes. Patients and families will repeat visits if they feel satisfied, on the contrary will be disappointed, angry and hurt if dissatisfied.Methods: This study is a quantitative descriptive of a study using primary data and secondary data. The primary data obtained through interviews, questionnaires on each ward in the Hospital Nur Hidayah Bantul, Yogyakarta. While secondary data obtained from the data through the document. Results: that significant value for comfort dimension (X1) is greater than the value of Î± (0.05) for 0284 from the test showed that there was no influence on the decision of inpatients in using the services of Nur Hidayah Hospital in Bantul, Yogyakarta. For information dimensions variable (X2) obtained significance value (sig) is smaller than the value of Î± (0.05) of 0.038., Meaning that there is the effect of variable dimensions of information (X2) against the decision of the patient (Y) hospitalization in using the services of the Hospital Nur Hidayah Bantul, Yogyakarta. For variable dimensions of human relationships (X3) values obtained significance value (sig) is smaller than the value of Î± (0.05) 0.000. This means that there is influence of variable dimensions between humans (X3) against the decision of the patient (Y) hospitalization in using the services of Nur Hidayah Hospital in Bantul, Yogyakarta.From the test results obtained value F kesil significantly more than the value of Î± (0.05) 0.000. This means that the variable dimension of comfort (X1), the dimensions of information (X2), and the dimensions of human relationships (X3) simultaneously have significant influence on the decision of the patient (Y). And the results of the t test can be concluded that the most dominant variable is a variable dimension of human relationships (X3) with sig level of 0.000.